Involvement of mediodorsal thalamus and its related neural circuit in pain regulation in mice - Chu-han Liu; Hui-jie Feng; Fei Peng; Shan Wang; Liu-jie Zhao; Hui Zhu; Xue-ying Dou; Ting Yuan; Chuang Li; Nan Zhou; Wen-xin Zhang; Xuan-ren Wang; et al. (Neurobiology of Disease)
The mediodorsal thalamus (MD) constitutes an integral component of the medial nociceptive transmission system, although its precise role and related neural pathway in pain processing remains incompletely elucidated. While anatomical studies have confirm reciprocal projections between the MD and anterior cingulate cortex (ACC), the functional contribution of ACC-MD neural circuitry to nociceptive regulation has not yet been systematically investigated. In this study, we used immunohistochemistry, pharmacogenetic manipulations, and multidimensional behavioral assessments to investigate the role of the MD and ACC-MD pathway in pain modulation. The MD can be activated by nociceptive stimuli, and mediates both exteroception-evoked reflexive-defensive reactions and interoception-mediated self-caring responses. Chemogenetics activation of the MD or the ACC-MD pathway induced hyperalgesia alongside aversion and anxiety-like behaviors. While inhibiting both alleviates pain and emotional comorbidities in neuropathic pain mice. These results identify a cortico-thalamic descending pathway that facilitates pain and emotional comorbidity, providing mechanistic insights for the developing neuromodulaion-based therapies against refractory neuropathic pain.